COMPOUND MEDICINE AND PANCH DICTIONARY: A FUTURE VISION - Sharma, Dipika; Pramod (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The relation of compound medicine and panch dictionary is associated with Indian philosophy and Ayurveda. Compound therapy is an ancient Indian science, which uses the principles and techniques of yoga for the balance of body, mind and soul. This research paper studies ways to maintain health from Panch Kosh through compound medicine. The relationship of compound therapy and punch dictionary is important for the entire health of the individual. The physical, mental and spiritual health of the person improves the physical, mental and spiritual health of the person through compound therapy. In this research paper, we will analyze the relationship between compound medicine and Panch Kosh and try to understand its importance from future point of view.